High‐Power Supercapacitive Properties of Graphene Oxide Hybrid Films with Highly Conductive Molybdenum Disulfide Nanosheets. Issue 12 (22nd September 2015) - Byun, Segi; Sim, Dong Min; Yu, Jin; Yoo, Jung Joon
Abstract: By introducing a graphene oxide (GO) sheet as a phase stabilizer and a mechanical supporter, MoS2 /GO hybrid films consisting of a high concentration of distorted 1T‐MoS2 are successfully fabricated through a post‐annealing process in air with the form of a restacked film. After the annealing process, the MoS2 nanosheets undergo direct binding with the oxygen functional groups of GO, maintaining their highly conducting 1T phase and leading to distorted 1T‐MoS2 or 1T′‐MoS2 . A hybrid film‐based supercapacitor reveals significantly enhanced electrochemical properties, such as an ultrahigh volumetric power density (≈207 W cm −3 ), high volumetric capacitance (≈380 F cm −3 at 10 mV s −1 ), superior rate capability, and a semi‐permanent cycle life (95 % retention after 10 000 cycles) in an aqueous electrolyte. Abstract : Channel the power : Ultrahigh‐power supercapacitive behavior of MoS2 /graphene oxide (GO) hybrid film consisting of a high concentration of distorted 1T‐MoS2 is demonstrated by utilizing the GO as a phase stabilizer and mechanical supporter. The hybrid‐film‐based supercapacitor reveals a superior electrochemical performance, owing to the high electrical conductivity of distorted 1T‐MoS2 in the hybrid film, functioning as efficient charge transporters and electrolyte channels.